Sentiment Analysis of User Comments on Vidio.com Digital Streaming Platform in Indonesia - Violinna Hutagalung; Hari Soetanto (LifeSciFi, 2026)
The development of digital streaming platforms has transformed the way people access entertainment, including in Indonesia, making sentiment analysis of user experience crucial for evaluating service quality. This study aims to analyze Vidio.com user sentiment based on 173,868 comments during April 2026 and identify the distribution of sentiment and key factors influencing user perceptions. The method used is lexicon-based sentiment analysis with data preprocessing and classification of positive, negative, and neutral polarities using a computational approach on large-scale text data. The results show that sentiment is dominated by negative (52.3%), followed by neutral (44.3%) and positive (3.4%), with the main issues stemming from ad interruptions and technical issues such as buffering and content playback. These findings indicate that user experience is still influenced by monetization strategies and infrastructure quality, particularly regarding excessive advertising. In conclusion, improving service quality and optimizing advertising strategies have important implications for platform development to increase user satisfaction and engagement. The implication is that the results of this study can be used as a basis for data-based decision-making in improving user experience through improving streaming systems, reducing ad interruptions, and strengthening continuous sentiment evaluation to support business strategies that are more responsive to user needs.